THE FREQUENCY AND SEVERITY OF COMPLICATED PYELONEPHRITIS AFTER ENDOSCOPIC INTERVENTIONS FOR UROLITHIASIS AND ITS RISK FACTORS - F.A. Akilov; Sh.I. Giyasov; A.R. Ruzibaev; I.B. Ziyaev; A.A. Rakhimbaev (Central Asian Journal of Medicine, 2023)
Background. Despite to the improvement of endoscopic instruments and intervention techniques, compliance with preventive measures of intra-and postoperative complications, the problem of the management of complicated urinary tract infections after interventions still remains as a very urgent problem. Purpose of the study. To evaluate the effectiveness of the preventive measures taken to reduce the frequency and severity of intra- and postoperative complications and determinate other causative factors in the development of acute complicated pyelonephritis after treatment of urolithiasis by endoscopic surgery. Materials and methods. A prospective analysis of the results of 220 X-ray endoscopic operations performed for kidney and upper urinary tract stones in the Republican Specialized Scientific-Practical Medical Center of Urology (RSSPMCU, Tashkent, Uzbekistan) during the period of 2019-2020 was carried out. The mean age of the patients was 44.3±14.8 (8-78 years) years. "simple" stones were in 112 (51%) patients, with 14.1±0.57 mm in size, "complex" - in 108 (49%), with 41.6±1.76 mm in size. During the examination, the initial infection of the urinary tract was found only in 194 patients (88.2%). From these, leukocyturia without bacteriuria was found in 59 (26.8%) patients, leukocyturia with bacteriuria in 135 (61.4%) patients, while only in 46 (20.9%) patients were revealed growth of microflora. Holmium laser lithotripsy was performed for single stones, pneumatic and ultrasonic lithotripsy were performed for staghorn and multiple stones, while the size of the nephroscope was 24 Ch-26 Ch, Amplatz - 30 Ch. Results. An analysis of the frequency of intraoperative complications showed that 23 (10.5%) had moderate bleeding during the intervention, which did not required additional interventions and blood transfusion, the «stone-free rate» (SFR) was 87.7%. The number of postoperative complications were 30 (13.6%), according to Clavien: I - 1 (0.5%), II - 19 (8.7%), IIIa - 5 (2.3%), IIIb - 3 (1 .4%), IVa - 2 (0.9%), V-0. The most common complication was acute complicated pyelonephritis, which revealed in 19 (8.7%) patients. All complication was eliminated conservatively. Conclusions. It was possible to improve measures for the prevention of infectious and inflammatory complications after endoscopic interventions in urolithiasis due to the monitoring and systematization of complications, as well as the study of the causes of their development. Among our patients, the frequency of complicated pyelonephritis depended on the initial infection of the urinary tract, as well as on the type of access to the stone and the duration of the intervention. The last two factors, in turn, depended on the complexity of the kidney stone.